Medicine then and now - Spilsbury, Louise (Oxford University Press, 2010)
These motivating non-fiction readers are rich in content and beautifully illustrated. Fascinating information in carefully graded language appeals to a broad range of students and supports English across the curriculum, making the series perfect for CLIL (Content and Language Integrated Learning).